Electrochemical Modeling of Iodide Oxidation in Metal-Halide Molten Salts. Issue 12 (10th December 2021) - Lee, Rose Y.; Percival, Stephen J.; Small, Leo J.
Abstract : The oxidation of iodide in NaI-AlBr3, NaI-AlCl3, and NaI-GaCl3 molten salts was analyzed using simulation software to extract relevant kinetic parameters. The experimental oxidation potentials were ordered AlCl3 < AlBr3 < GaCl3, with higher oxidation potentials correlating with softer Lewis acidity of the metal halide. An iodide oxidation and metal halide speciation model was developed and simulated to fit the electrochemical response, enabling determination of electrochemical charge transfer parameters and chemical equilibrium constants. NaI-AlBr3 displayed the fastest electron transfer rates yet showed the lowest current densities. All salts revealed smaller than expected current densities, explained by equilibrium between various species, where some are not electrochemically active at the studied potentials. These equilibrium reactions are due to the various metal halide species, controlling the reactant concentration of iodide and the resultant current. We hypothesize the electrochemically active iodide species, present as a metal halide monomer (MX3 I − ), is decreased dramatically from the expected concentration, sequestered as a more stable metal halide dimer species (M2 X6 I − ) with a higher oxidation potential. Traditional Tafel analysis of the experimental data supports the validity of the simulations. These results increase understanding of iodide oxidation in low-temperature Lewis acidic molten salts and inform task-specific molten salt design.